2019
DOI: 10.1021/acsomega.9b02031
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4-Mediated Synthesis of Cu2O To Obtain Porous Composites with Improved Visible Light Photocatalytic Degradation of Organic Dyes

Abstract: A highly porous architecture of graphitic carbon nitride g-C3N4/Cu2O nanocomposite in the form of cubes with a side length of ≈ 1 μm, large pores of 1.5 nm, and a high surface area of 9.12 m2/g was realized by an optimized in situ synthesis protocol. The synthesis protocol involves dispersing a suitable “Cu” precursor into a highly exfoliated g-C3N4 suspension and initiating the reaction for the formation of Cu2O. Systematic optimization of the conditions and compositions resulted in a highly crystalline g-C3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 69 publications
(128 reference statements)
4
19
0
Order By: Relevance
“…XRD spectra of Cu 2 O NPs showed the diffraction peaks appeared at a 2θ value of 29.48°, 36.38°, 42.20°, 61.32°, 75.26° and 76.30° corresponds to the (110), (111), (200), (220), (311) and (222) characteristic planes, and confirmed that all the diffraction peaks in the XRD spectrum correspond to the standard pattern of cuprous oxide cubic crystal system (PDF#05-0667, cell parameter a = 0.4269 nm) ( Fig. S1), and had high diffraction intensity and sharp peak shape, indicating that the products had good crystallinity 25,26 . It can also be seen from the XRD spectra that the synthesized nanoparticles had no impurity peak, indicating that the product had a single crystal shape and high crystal purity ( Fig.…”
Section: Resultssupporting
confidence: 57%
“…XRD spectra of Cu 2 O NPs showed the diffraction peaks appeared at a 2θ value of 29.48°, 36.38°, 42.20°, 61.32°, 75.26° and 76.30° corresponds to the (110), (111), (200), (220), (311) and (222) characteristic planes, and confirmed that all the diffraction peaks in the XRD spectrum correspond to the standard pattern of cuprous oxide cubic crystal system (PDF#05-0667, cell parameter a = 0.4269 nm) ( Fig. S1), and had high diffraction intensity and sharp peak shape, indicating that the products had good crystallinity 25,26 . It can also be seen from the XRD spectra that the synthesized nanoparticles had no impurity peak, indicating that the product had a single crystal shape and high crystal purity ( Fig.…”
Section: Resultssupporting
confidence: 57%
“…No substantial changes were noticed in the structures and active functional groups of the photocatalyst before and after reused, which speci es that the g-C 3 N 4 /ZnO/Cu 2 O heterostructured photocatalyst was greatly stable. The as-obtained photocatalytic activity of this work was better for with the formerly reported photo-degradation [38,[45][46][47]. Also, the photocatalytic performance of g-C 3 N 4 /ZnO/Cu 2 O composite photocatalyst was greater when compared to the commercial P25 TiO 2 NPs [48].…”
Section: Photocatalytic Recycling Stabilitysupporting
confidence: 47%
“…Based on the photo-degradation outcomes, a possible charge transfer mechanism of g-C ), and then ˙O 2 − radicals and h + are capable to openly oxidize the organic impurities (RhB dye) owing to their great oxidative ability reagents for RhB [45] dye to make it degrade eventually. Thus the synergistic separation of photo-excited e − /h + pairs could be captured on the g-C 3 N 4 surface of the PCs to yield a variety of reactive oxygen species (ROSs) to effect the desired degradation in the aqueous dye solution [58].…”
Section: A Mechanism For Photocatalytic Dye Degradationmentioning
confidence: 99%
“…In Figure 5 b, the high-resolution spectra of C 1s could be fitted into three peaks at about 283.2, 284.7, and 288.2 eV in Ag/CN-8, which were assigned to the aromatic carbon atom, the C–C coordination, and the N=C—N coordination, respectively. 36 39 Figure 5 c shows that the N 1s spectra could also be separated into two peaks centered at 398.7 and 400.3 eV in Ag/CN-8, which were ascribed to C—N=C, N–(C) 3 , and N–H, respectively. 40 42 Compared with CN-1, the C 1s and N 1s peak of Ag/CN-8 shifted to a higher binding energy, which could be assigned to the interaction between Ag and g-C 3 N 4 .…”
Section: Results and Discussionmentioning
confidence: 99%